2018
DOI: 10.1186/s40066-018-0230-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate-smart agricultural practices on household food security in smallholder production systems: micro-level evidence from Kenya

Abstract: Background: Climate change in Sub-Saharan Africa has had a negative impact on agricultural production leading to food insecurity. Climate-smart agricultural (CSA) practices have the potential to reverse this trend because of its triple potential benefits of improved productivity and high income, reduction or removal of greenhouse gases and improved household food security. Hence, we empirically find the determinants of choice and the effect of CSAs on household food security among smallholder farmers in Kenya.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
44
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 21 publications
12
44
3
Order By: Relevance
“…Additionally, farmers' education could enhance the productivity of agricultural extension services, as educated farmers could be more receptive to and productive with new agricultural innovations or practices. However, the result obtained is in contrast with the finding of Wekesa et al [17], who reported a negative influence of years of schooling on the choice of CSA package. Wekesa et al [17] argued that educated farmers would opt out of a CSA package if it does not offer risk reduction measures which could protect their investment against the risks of climate change.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Additionally, farmers' education could enhance the productivity of agricultural extension services, as educated farmers could be more receptive to and productive with new agricultural innovations or practices. However, the result obtained is in contrast with the finding of Wekesa et al [17], who reported a negative influence of years of schooling on the choice of CSA package. Wekesa et al [17] argued that educated farmers would opt out of a CSA package if it does not offer risk reduction measures which could protect their investment against the risks of climate change.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding suggests that small-scale farmers, who are more open to the integration of different farming techniques, would adopt more CSA practices compared to their counterparts who rely solely on one farming enterprise. Being open to the combination of varying farming techniques creates a promising and conducive platform for mainstreaming CSA [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 4, the impact of adaptation on crop yields is determined by differencing column (c1) and column (c2). The results portray that adaptation grants higher yields as compared with not adapting, which is consistent with several studies (for example Asrat and Simane 2017;Mohammed et al 2017;Bedeke et al 2018;Di Falco and Veronesi 2018;Gorst, Dehlavi, and Groom 2018;Khanal et al 2018;Nonvide 2018;Wekesa, Ayuya, and Lagat 2018). That is, farmers who actually adopted would have gained lower if they had not adapted; and those farmers who actually did not adapt would have gained higher if they had adapted (counterfactual).…”
Section: Impact Of Adaptation On Crop Yieldsupporting
confidence: 88%
“…Numerous studies have also examined the impact of climate change adaptation on crop productivity and income (see e.g. Asrat and Simane 2017;Mohammed et al 2017;Amare and Simane 2018;Di Falco and Veronesi 2018;Gorst, Dehlavi, and Groom 2018;Khanal et al 2018;Nonvide 2018;Wekesa, Ayuya, and Lagat 2018;Cholo et al 2019). However, the current study differs from these studies in at least four areas.…”
Section: Introductionmentioning
confidence: 94%